Determination of ethanol using the automatic enzymatic method - Varo Galvañ, Pedro; Rodríguez Pastor, Manuel (BrewingScience, 2001)
The enzymatic Emit® ETS ® Plus Ethyl Alcohol Assay (Emit) was used for the quantitative analysis of the ethanol content in low-alcohol beer. The assays were designed for use with the Syva ETS® Plus analyzer. The method is based on the enzymatic determination of ethanol with alcohol dehydronase. Repeatability (r₉₅) and reproducibility (R₉₅) values fo aqueous controls (target value 0.05–0.06 v/v ethanol) were 0.006 and 0.011 respectively. In low-alcohol beer (target value alc. less than 0.5% vol.), r and R values were 0.017 and 0.038 respectively. The Emit assays were found to be rapid, precise and accurate for the determination of ethanol in low-alcohol beer. The method was tested under real conditions for the determination of ethanol in low-alcohol beer.